(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Chen TV, Tuan ND, Triet NT, An NH, Nguyen PTT, Hai NTT, Nhi NTT, Co NQ, Nhi HTH, Huong HV, Phuong TTB, Nhung NTA. 2022. Morphological and molecular characterization of Distichochlamys citrea M.F. Newman in Bach Ma National Park, Thua Thien Hue Province, Vietnam. Biodiversitas 23: 2066-2079. Distichochlamys citrea (Black Ginger or gung den) is a medicinal plant endemic to Vietnam. However, this species is not easily identified due to the lack of a detailed description. Therefore, this study aimed to characterize morphological and molecular aspects of D. citrea from Bach Ma National Park, Vietnam. Six representative plants were selected for the following analyses. Macromorphological features were observed and compared with previous studies. The rhizomes, roots, petioles, and leaves were then histologically analyzed using iodine green-carmine staining. The ground rhizomes and leaves were also microscopically examined for powder characteristics. Finally, the D. citrea DNA barcode was amplified by Internal Transcribe Spacer (ITS) primers. Macromorphologically, D. citrea differs from other Distichochlamys species. Black Ginger, particularly, has elongated rhizomes (with scars from the shoots of previous years), green leaves, spread inflorescences, and yellow labellum (with deep slits). Additionally, D. citrea’s micromorphological structures (epidermis, exodermis, hypodermis, cortex, endodermis, and root pith) are similar to the genus Zingiber. However, the absence of calcium oxalate and silica crystals in the root is unique and can be used to distinguish this plant from other Zingiberaceae members. The sequenced amplicons (96.54% similar to Genbank’s D. citrea ITS) demonstrated the ITS marker’s ability to identify Black Ginger.